Probiotic efficacy and mechanism of a pigeon derived Ligilactobacillus salivarius strain in promoting growth and intestinal development of pigeons - Zhao, Puze; Li, Yumei; Yang, Yuwei; Xiao, Qingxing; Zhang, Ziyi; Hong, Xiaoqing; Ni, Hongyu; Xia, Zhuxuan; Zhan, Kun; Yang, Sibao; Zhang, Yonghong (Frontiers in Microbiology, 2025)
BackgroundWith the gradual rise of antibiotic-free farming practices, the exploration of novel, green, and low-pollution alternatives to antibiotics has become one of the key research focus in the field of agricultural science. In the development of antibiotic alternatives, probiotics, particularly host-associated probiotics, have been found to play a significant role in enhancing the production performance of livestock and poultry. However, research on and application of probiotics specifically for meat pigeons remain relatively underdeveloped.ObjectiveTo assess and investigate the probiotic efficacy and mechanisms during homologous lactic acid bacteria (LAB) transplant to host-pigeons, LAB strains with good probiotic properties were isolated from the intestinal contents of 28-day-old Mimas pigeons. And then measured the production indexes, intestinal flora, and intestinal transcriptomics of the hosts after instillation of LAB strains.MethodsA total of 360 at 1-day-old pigeons were randomly divided into four groups and gavaged 0.4 mL Ligilactobacillus salivarius S10 with concentration of 0, 108, 109, and 1010 CFU/mL, designated as the control group (CG), the low concentration group (LG), the medium concentration group (MG), and the high concentration group (HG), respectively.ResultsThe findings revealed that an optimal concentration of 109 CFU/mL L. salivarius S10, a dominant strain isolated and screened, enhanced the growth performance and intestinal development of young pigeons. 16S rRNA gene sequencing analysis demonstrated a significant increase in the abundance of Lactobacillus, Pantoea_A and Enterococcus_H and a significant reduction in the abundance of Clostridium_T in the pigeon ileum (p < 0.05) under selected concentration treatment. Transcriptomic profiling of the ileum revealed 1828 differentially expressed genes (DEGs) between CG and MG. Notably, DEGs involved in the MAPK signaling pathway, such as RAF1, PDGFRB, and ELK4, were significantly correlated with differential ileal bacteria, suggesting that modulation of intestinal flora can influence the expression of genes related to cell proliferation and differentiation in the ileum, which is potentially important in promoting the growth and development of pigeons.ConclusionLigilactobacillus salivarius S10 possesses the potential to be used as a probiotic for pigeons, which can influence the expression of gut development-related DEGs by regulating the intestinal flora, and further improve the growth performance of pigeons. This research provides a scientific foundation for developing pigeon-specific probiotics and promotes healthy farming practices for meat pigeons. Furthermore, it opens new avenues for improving the economic efficiency of pigeon farming.